Arabidopsis lipoxygenase 2 is essential for formation of green leaf volatiles and five‐carbon volatiles. Issue 7 (28th March 2016) - Mochizuki, Satoshi; Sugimoto, Koichi; Koeduka, Takao; Matsui, Kenji
Abstract : Plants biosynthesize a variety of bioactive lipid derivatives, such as green leaf volatiles (GLVs) and jasmonates (JAs). Here we identify a lipoxygenase 2 (LOX2) involved in GLV biosynthesis in Arabidopsis using mutant lines for each of the six LOX isoforms present in Arabidopsis. We found that formation of five carbon volatiles was also dependent on LOX2. LOX2 is known to be involved in formation of JA; thus, LOX2 is apparently versatile in function. The results in this study suggested that LOX2 activity is suppressed in intact cells but activated upon tissue damage to support the rapid GLV‐burst observed in wounded leaves. Abstract :